Diagnosis and management of intramural ectopic pregnancy - Qian Hu; Mohammed Sharooq Paramboor; Tao Guo (IMR Press, 2021)
Background: Intramural pregnancy is a rare form of ectopic pregnancy where the embryo is implanted within the myometrium, separate from the endometrial cavity. Preoperative diagnosis of intramural pregnancy is difficult and it can easily be misdiagnosed for other diseases such as intrauterine pregnancy or gestational trophoblastic disease. Medical therapy and surgery are used to treat intramural pregnancy, with surgery often being performed via laparotomy and also including hysterectomy. Case: We present a case of intramural pregnancy that was misdiagnosed and wrongly managed by a local hospital. It was finally diagnosed correctly and managed in our hospital by combining hysteroscopy and laparoscopy under the guidance of intra-abdominal ultrasound. Our experience again highlights the difficulty in diagnosing intramural pregnancy preoperatively due to the lack of standard diagnostic criteria. This can in turn lead to inappropriate treatments. Earlier surgical intervention would allow faster diagnosis and also simultaneous treatment of the disease. The majority of intramural ectopic pregnancies have high blood flow that can cause severe hemorrhage and are therefore treated by medication or laparotomy and hysterectomy. Conclusion: Our experience reveals that a minimally invasive procedure is also safe and effective in select cases where advanced endoscopic expertise is available.